Validação contínua do processo de diagnóstico audiológico e intervenção em bebês e crianças com deficiência auditiva - Souza, Juliana Luz (2023)
Introduction: New challenges are presented to the area of pediatric audiology, with the access of increasingly younger children to the clinic, since the work with these children requires greater attention from the professional in the hearing aids fitting, as well as in the process of development of infants and young children. Limitations and inaccuracies throughout the diagnostic process may compromise all subsequent procedures in the intervention process. Objective: To analyze the continuous validation of the process of audiological diagnosis and intervention in infants and children with hearing loss based on observation of auditory behavior, speech perception and hearing and language skills after hearing aids fitting. Method: This is an individual operative descriptive, intervention, cross-sectional and prospective research, of a quantitative nature, approved by the University's research ethics committee. The research subjects were 12 children aged up to 36 months, with audiological diagnosis of bilateral sensorineural hearing loss, grouped into G1 (subjects with SII 65 dB up to 35%) and G2 (subjects with SII 65 dB above 54%). The diagnostic evaluation data were collected from the service's records and the steps of the hearing aids fitting were described throughout the initial intervention process. Patients were selected based on the availability of access to the service for the evaluation. Audiometry of visual reinforcement was carried out and the instruments It-MAIS, MUSS, LittleEars-2, hearing and language categories, where applied with those responsible for the children, in addition to the socioeconomic characterization questionnaire. Results: The average age of the audiological diagnosis was 4.33 months. The results of all the children were consistent in the diagnostic tests, with the exception of two subjects from G2. Children from G1 performed worse than their peers from G2 in the applied instruments. In the second evaluation, the children from G2 significantly increased the MUSS score and their general performance increased as the use of hearing aids increased, without statistical significance. Conclusion: The auditory behavior validated the processes of diagnosis and auditory intervention of the research subjects and the application of the instruments proved to be suitable for monitoring the development of hearing and language skills in young children